UPAYA MENINGKATKAN KUALITAS PELAYANAN MELALUI KETERAMPILAN PRAMUSAJI DAN PEMAHAMAN MENU DI HOTEL COURTYARD BY MARRIOTT BANDUNG - Muhammad Azka Ashidiq; Dendi Gusnadi (Media Bina Ilmiah, 2024)
In the hospitality industry, customer satisfaction is very important. The aim of this research is to determine the quality of food and beverage (F&B) services at the Courtyard Hotel Bandung. To collect data, this research used a qualitative approach using direct observation, interviews and documentation studies. The main findings show that the Courtyard Bandung Hotel's F&B service is very good for most visitors. Service quality consists of employee friendliness, speed of service, quality of food and drinks, and location cleanliness. Managing time and consistency of service is still a problem that needs to be fixed. According to this research, hotel management must continue to improve the quality of F&B services if they want to maintain and increase customer satisfaction and strengthen the hotel's image.